Answer:
(a) GF = 1.522 x (10 ^ -7) N
(b) GF = 2.032 x (10 ^ -4) N
Step-by-step explanation:
The magnitude of the gravitational force follows this equation :
GF = (G x m1 x m2) / (d ^ 2)
Where G is the gravitational constant universal.
G = 6.674 x (10 ^ -11).{[N.(m^ 2)] / (Kg ^ 2)}
m1 is the mass from the first body
m2 is the mass from the second body
And d is the distance between each center of mass
m2 is a particle so m2 it is a center of mass itself
The center of mass from the sphere is in it center because the sphere has uniform density
For (a) d = 19 m
GF = {6.674 x (10 ^ -11).{[N.(m ^ 2)] / (Kg ^ 2)} x 8.4 x (10 ^ 4) Kg x 9.8 Kg} / [(19 m)^ 2]
GF = 1.522 x (10 ^ -7) N
For (b) d = 0.52 m
GF = 2.032 x (10 ^ -4) N
Notice that we have got all the data in congruent units
Also notice that the force in (b) is bigger than the force in (a) because the distance is shorter